2006
DOI: 10.1063/1.2183359
|View full text |Cite
|
Sign up to set email alerts
|

Metal–polymer composite with nanostructured filler particles and amplified physical properties

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 15 publications
1
63
2
Order By: Relevance
“…The slope for all Ni-PDMS curves is 600  G . Using Equation (2) and considering Poisson's ratio with value of ~ 0.35 for polymer composites we obtain 180  Γ , which is higher than that reported for QTC TM materials (~105) (Bloor et al, 2006) and comparable to Au-coated Ni-epoxy composites (~200) (Martin et al, 2003). The gauge factor of Ni-PDMS is a characteristic parameter for this composite and does not change by concentration.…”
Section: Mechanical Propertiesmentioning
confidence: 76%
“…The slope for all Ni-PDMS curves is 600  G . Using Equation (2) and considering Poisson's ratio with value of ~ 0.35 for polymer composites we obtain 180  Γ , which is higher than that reported for QTC TM materials (~105) (Bloor et al, 2006) and comparable to Au-coated Ni-epoxy composites (~200) (Martin et al, 2003). The gauge factor of Ni-PDMS is a characteristic parameter for this composite and does not change by concentration.…”
Section: Mechanical Propertiesmentioning
confidence: 76%
“…For example, during compression the sample resistance can fall by a factor of > 10 14 . It has also been shown that charge concentration at the tips of the spiky filler particles results in large electric fields, so that charge transport occurs through electric field assisted quantum tunneling rather than by direct contact between the particles [9,10]. Granular QTC™ can be used to produce a vapor sensor which is capable of solving some of the issues highlighted above.…”
Section: A Conduction Mechanisms and Vapor Sensing In Conductive Polmentioning
confidence: 99%
“…They are outstandingly selective in relation to Fe and Cu and they can sorb very small concentrations of Au, Pd and Pt from the solution which gives them a complete ecological and economic feasibility and the advantage compared to existing technologies. Their special value in fundamental research is that bionanonoblemetals polymers are synthesized for use in nanoelectronics (Bloor et al, 2005(Bloor et al, , 2006Burda et al, 2005;Cao et al, 2009;Dai et al, 2006;Feng et al, 2010;Hoppe et al, 2006;Ingrosso et al, 2010;Kim et al, 2007;Lai et al, 2008;Lazzari & Lopez-Quintela, 2003;Li et al, 2010;Liu, T et al, 2003;Liu, P. et al, 2009;Sarkar et al, 2010;Sathishkumar et al, 2009;Thompson, 2007;Yaghi et al, 2003;Yin et al, 2009;Yoon et al, 2008;Zhang et al, 2009;Zubarev et al, 2006) and cancer nanotechnology (Cai et al, 2008;Chen et al, 2008;Daniel & Astruc, 2004;De et al, 2008;Patraet al, 2007;Popovtzer et al, 2008;Xia et al, 2003;Yang et al, 2008;Love et al,2005).…”
Section: The Application Of New Grafted Cellulose and Lignin Copolymementioning
confidence: 99%